STUDENTS SPEAKING DIFFICULTIES IN ENGLISH PRESENTATIONS AT SMA PUJER - melinia, Melinia dwi Intan fransiska; Hatip, Mochammad; Rasukir, Muhlisin (English Education Program, Education Faculty, Universitas Nurul Huda, 2024)
Students prefer their native language over English in everyday communication. While initial conversations in English go smoothly, difficulties arise as the conversation progresses. Especially, during presentation students often find it is difficult. This study set out to discover students speaking difficulties in English presentation. A qualitative method was used to summarize the data that was obtained from the outcome. The primary data in this research will take from that will be given for students at SMA Pujer in academic year 2022/2023. The data obtained from questionnaire that distributed to all students. The data obtained from the questionnaire was analyzed by using descriptive statistic.Those difficulties were categorized into several groups, namely: Speaking anxiety, topic and vocabulary, time management, grammar mastery and keeping the audience.Most of the students who had problems noted that giving an oral presentation was particularly tough because of their fear and lack of confidence. Students can overcome their challenges by bringing a note with them during presentations, memorising the material, and avoiding eye contact.